Back to Work: The Unequal Effects of the COVID-19 Pandemic on Ecuador's Labor Market - Sergio Olivieri; Francesc Ortega; Ana Rivadeneira (Institute of Labor Economics (IZA), 2023)
Using the 2021 and 2022 HFPS for Ecuador, the paper investigates the labor market trajectories of different socio-economic groups. The analysis shows that the employment of older individuals, less-educated workers, and women fell disproportionately. However, while the recovery between 2021 and 2022 was slower for the first two groups, females experienced a faster rebound, even though still remained below pre-pandemic levels. The estimates also suggest that the recovery was slower for parents, despite the practically complete return to in-person instruction. The paper's more novel findings refer to the employment of Venezuelan migrants. The pandemic lowered their employment rate by a similar magnitude as for Ecuadorians. However, between 2021 and 2022, the employment and average work hours of Venezuelan migrants increased substantially faster than for natives, possibly because of their lower ability to rely on savings. The data also show that most of the increase in their labor supply stemmed from Venezuelan households without children, suggesting that Venezuelan families were less able to cope with the uncertainty associated with the return to in-person schooling.
Keywords: O15; J61; D3; 330; migration; COVID-19; Ecuador; forced migration; Venezuelans